Bauchi State Integrated Rural Development Authority Planning Department, 1989 Action Plan Volume V : livestock services, rural roads, rural water, rural electrification and community development (Bauchi, Nigeria : Bauchi State Integrated Rural Development Authority, 1989)
This is the Bauchi State Integrated Rural Development Authority Planning Department, 1989 Action Plan Volume V which focused on livestock services, rural roads, rural water, rural electrification and community development.
lje 14/3/19
Arch.
Keywords: Rural development; Livestodk services; Electrification; Road construction; Bauchi State (Nigeria)